Study of natural mechanisms for the supply of transported materials to the Ag. Varvara coast (Lesvos island) - Lykoudi, E.; Antoniou, M. (Bulletin of the Geological Society of Greece, 2007)
The shaping of a coast is the result of the interaction of ground and marine factors. To study the formation mechanism of the coast, it is necessary to study both the characteristics of the source from which the transported materials originate, that is the rivers discharging in it, and the characteristics of the receiver of these materials, that is the coastal zone. The results of such a study contribute to the application of a administrative action plan to this system, based on the principles of the integrated administration and the viable evolution. In this work the dynamics that shapes the coast ofAg. Varvara are examined. To this purpose, both the natural supply mechanism of the Ag. Varvara ’s coastal zone with materials from the Voulgaris river and the settlement mechanism of these materials are under investigation. The most significant factors influencing the characteristics of the Voulgaris river - which is the main materials supplier of the coast – and shaping the evolution of the Ag. Varvara ’s coatal zone, are the catchment area as well as the interactions taking place in it, the type and the quantity of the transported material, (geological factor), the tectonic movements influencing the shaping of the area, and finally the climatic conditions. The geomorphologic-morphotectonic analysis points to the fact that, while there is substantial supply of material to the river bed, only a small percentage of that is being transported to the coast. This is attributing to the diminished transportation capability of the river. Other factors contributing to this are the longer than expected length of the river bed, its small slopes, an the low rainfall level in the area